Evaluasi dan Perbaikan Proses Bisnis menggunakan Business Process Improvement (BPI) (Studi Kasus: PT Cita Intrans Selaras (CITILA)) - Bella Karina Sari; Ismiarta Aknuranda; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
PT Cita Intrans Selaras (CITILA) is a publishing company that focuses on publishing educational books. PT CITILA has a Publisher Division that is involved in the process of processing raw manuscripts into printed books. Problems that occur in this company include the flow of the script is slowed and there is a typing error in the title, which causes reprinting. Then, it is necessary to identify problems in detail and improve existing conditions through improving business processes. The methodology used to improve business processes is Business Process Improvement (BPI) and applying standards (BPMN) for business process modeling and Failure Mode and Effects Analysis (FMEA) to analyze and evaluate business processes. Improvements were made in accordance with the help of Streamlining Tools within BPI, including adapting Upgrading and Simplification. One of the results of the improvement obtained is that there are activities that utilize email sending. Then, the modeling of the current business process (as is) and the business process modeling recommendations (to be) are simulated and validated in order to find out how much time increases (%) are obtained. The results of the simulation show the time efficiency of the four business processes namely script review business processes with an efficiency of 55.93%, business process editing of scripts by 30.02%, business processes designing book layouts by 30.91%, and business processes designing covers books by 5.70%.